HUBUNGAN POLA BERMAIN DENGAN MEMORY DIGIT ANAK AUTISM SPECTRUM DISORDERS DI SURAKARTA: RELATIONSHIP BETWEEN PLAY PATTERNS AND DIGIT MEMORY IN CHILDREN WITH AUTISM SPECTRUM DISORDERS IN SURAKARTA - Risqa Wulandari; Purnaningrum, Windiarti Dwi; Putri, Anggi resina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2025)
Autism spectrum disorders are characterized through impaired social and communication skills, repetitive behaviors, unusual hobbies and differences perception of sensory stimulation. Developmental disorders in kids with ASD can affect the early development of play skills, resulting in unusual or limited play patterns in children with ASD. The decline in cognitive abilities in children with ASD is associated with working memory, which is the ability to remember something. The research design used is correlational with a cross-sectional approach. The sample for this study consisted of 32 people interviewed using the purposive sampling technique. Facts evaluation changed into accomplished using Pearson's product moment parametric statistical test. Play patterns of kids with autism spectrum disorders in Surakarta are on the average threshold, while the digit memory ability of youngsters with autism spectrum disorders in Surakarta is under the common restrict.